Development of Mathematics Learning Tools Based on Realistic Mathematics Education to Improve Mathematical Critical Thinking Ability for Class VII Middle School - Hendrajah, Apdyan Dwi; Yerizon, Yerizon; Arnawa, I Made (Journal of Social Research, 2023)
This research aims to produce a learning tool that is valid, practical, and effective. This learning tool contains material for flat-sided shapes. This research is a development research using the Plomp model, which includes Preliminary Research, Prototyping Stage, and Assessment Stage. The instruments used in the study were learning device assessment sheets to measure validity, educator response questionnaires, student response questionnaires, learning implementation observation sheets to measure practicality, and tests of critical thinking skills to measure effectiveness. Learning devices are said to be valid and practical if they meet at least good criteria (average score more than 3.40) and the percentage of learning implementation is at least 70%, while it is said to be effective if the percentage of student completeness is more than 60%. The learning device was implemented at As-Salam Islamic Middle School, Tanjung Gadang, Sijunjung Regency with the object of research being students of class VII Marwah. This research produced a set of learning tools in the form of lesson plans and worksheets for six meetings. Learning tools meet valid criteria with an average score of 3.52 for lesson plans and 3.52 for worksheets from a maximum score of 4.00. Learning tools meet the very practical criteria with an average score of 80% for the teacher response questionnaire and 88.17% for the student response questionnaire with a maximum score of 100%, while the average percentage of learning implementation is 83.21%. Learning devices meet the criteria of effectiveness with a percentage of completeness of student learning outcomes of 75.57%.